2022
DOI: 10.1371/journal.pmed.1003968
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mexican warning label nutrient profile on food products marketed in Mexico in 2016 and 2017: A cross-sectional analysis

Abstract: Background Different nutrient profiles (NPs) have been developed in Latin America to assess the nutritional quality of packaged food products. Recently, the Mexican NP was developed as part of the new warning label regulation implemented in 2020, considering 5 warning octagons (calories, sugar, sodium, saturated fats, and trans fats) and 2 warning rectangles (caffeine and non-nutritive sweeteners). The objective of this cross-sectional study was to evaluate the Mexican NP and other NPs proposed or used in Lati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…Considering the MNPM, only 3.2% of the products would not receive FoPNL, while by the BNPM, almost half of the products (43.3%) would be classified as healthy. These results corroborate with the results of other studies that compared the BNPM with the PAHO's NPM and/or MNPM and found higher percentages of foods classified as healthy for the first profile (27,35). Duran et al ( 27) evaluated a preliminary and less rigorous BNPM than the one approved by the Brazilian Legislation, used in the present study, and observed that 38% and 55% of the foods were classified as healthy (without FoPNL) by the PAHO's NPM and BNPM, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Considering the MNPM, only 3.2% of the products would not receive FoPNL, while by the BNPM, almost half of the products (43.3%) would be classified as healthy. These results corroborate with the results of other studies that compared the BNPM with the PAHO's NPM and/or MNPM and found higher percentages of foods classified as healthy for the first profile (27,35). Duran et al ( 27) evaluated a preliminary and less rigorous BNPM than the one approved by the Brazilian Legislation, used in the present study, and observed that 38% and 55% of the foods were classified as healthy (without FoPNL) by the PAHO's NPM and BNPM, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Duran et al ( 27 ) evaluated a preliminary and less rigorous BNPM than the one approved by the Brazilian Legislation, used in the present study, and observed that 38% and 55% of the foods were classified as healthy (without FoPNL) by the PAHO's NPM and BNPM, respectively. In the study conducted by Contreras-Manzano et al ( 35 ), who evaluated foods available in the Mexican market, about 20% and almost half of the products were classified as healthy by the MNPM and the BNPM, respectively. Despite the methodological differences between the aforementioned and the present study, it is possible to notice an overestimation of the percentage of products classified as healthy by the BNPM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PAHO NPM is classified as excessive if sodium accounts for ≥1 mg of sodium per 1 kcal, free sugars ≥10% of energy, total fat ≥30% of energy, saturated fat ≥10% of energy and trans‐fat ≥1% of energy 35 . The Mexican NPM is considered stricter 37 since it incorporates cut‐off points for energy (≥275 kcal for solids or ≥70 kcal for liquids) and for sodium (≥350 mg and ≥45 mg for non‐caloric beverages).…”
Section: Methodsmentioning
confidence: 99%